Dynamics of the Gifts of the Holy Spirit - Dziuba, Andrzej (Studia Teologiczne Białystok Drohiczyn Łomża, 2023)
Theology underlines that the gifts of the Spirit are given not only in the sacraments of baptism and confirmation, but they always accompany God's grace. The working of the Paraclete is always inscribed in the history of the Church and in the people of faith. However, it must be remembered that these are not new abilities, but tasks. The human response should be an openness of heart in order to develop a relationship with God and to improve one's virtues. The development of virtues takes place thanks to the operation of reason and free will, while the gifts of the Spirit are supernatural, i.e. they allow one to go beyond the promptings of natural reason and beyond the abilities of will. According to the prophet Isaiah, the gifts have the following order: wisdom, understanding, counsel, fortitude, knowledge, piety, and fear of God. Only a fuller biblical discernment allows a deeper understanding of them. Following this line of analyzes, the shown image allows us to recognize the continuous relevance of the gift of Pentecost, which is constantly being fulfilled in the pilgrim eschatological People of God of the New Covenant.